Strategic management theory : an integrated approach - Hill, Charles W. L.; Jones, Gareth R. (Boston : Houghton Mifflin, 1998)
This book is about: Introduction to strategic management; The nature of competitive advantage; Strategies; Implementing strategy; ...
Keywords: Business; Management; Strategic planning; Management -- United States -- Case studies; Strategic planning -- United States -- Case studies; Business planning -- United States -- Case studies